Determination of heart rate variability thresholds and their association with lactate threshold in novice female runners - Mustakoski, Iida (2023)
Endurance type exercise at different intensities induces various physiological changes in human body. For desirable training stimuli the exercise intensity should be chosen according to what are the physiological changes at which training is currently targeted. Exercise thresholds (ET) are intensity bounds that are separating the exercise intensities with different physiological functions. ETs can be determined from measurements conducted during graded exercise test. Traditionally, blood lactate concentration and/or ventilatory functions are measured and thresholds are determined based on changes seen on those parameters. For lactate and ventilatory measurements, applicable equipment and experienced testing personnel are needed. Thus, new methods which are more easily executed and noninvasive would be useful. The purpose of this study was to test the applicability of HRV threshold methods presented in previous studies in nonathletic, healthy females. In recent years, also other less invasive methods and physiological measures for threshold determination have been developed and tested. One of those is heart rate variability (HRV). In this study, the identifiability and reliability of heart rate variability thresholds (HRVT) compared to lactate threshold (LT) were tested. Lactate thresholds were determined according to the Finnish recommendations. Four methods were used for first heart rate variability threshold (HRVT1) and three methods for second heart rate variability threshold (HRVT2) determination. For HRVT1 determination RMSSD parameter of time domain analysis, HF power of frequency domain analysis, SD1 of Poincaré plot and DFA-a1 of detrended fluctuation analysis were used. Respectively, for HRVT2 determination HF power, SD2 and DFA-a1 were examined. Heart rate and speed at HRVT1 and HRVT2 determined by different methods were compared to HR and speed at LT1 and LT2, correspondingly. All the participants were adult female novice runners. There is currently a couple of previous studies investigating the reliability of heart rate variability thresholds. However, very few of them are conducted in females thus the results of the present study widen the knowledge about the applicability of HRVT methods among female population. According to the results, HRVTs are mostly identifiable in novice female runners. The only exception was HRVT2 determined using HF power which could only be identified in half of the participants. Considering the analysis methods used (correlations, paired differences, ICCs, linear regressions, Bland Altman -plots) the most reliable HRVT1 method for LT1 estimation seemed to be the one based on time domain analysis and its RMSSD variable. None of the HRVT2 methods used appeared superior to others and all showed quite low correlations and reliability when compared to LT2. In the future, it would be important to conduct more studies of this topic in female population with different and maybe more strictly standardized testing protocols. The applicability of HRVTs in practical training would also be relevant topic to be investigated.